Recurrence of Graves’ Disease: What Genetics of HLA and PTPN22 Can Tell Us - Vejrazkova, Daniela; Vcelak, Josef; Vaclavikova, Eliska; Vankova, Marketa; Zajickova, Katerina; Vrbikova, Jana; Duskova, Michaela; Pacesova, Petra; Novak, Zdenek; Bendlova, Bela (Frontiers in Endocrinology, 2021)
Background: Approximately half of patients diagnosed with Graves' disease (GD) relapse within two years of thyreostatic drug withdrawal. It is then necessary to decide whether to reintroduce conservative treatment that can have serious side effects, or to choose a radical approach. Familial forms of GD indicate a significant genetic component. Our aim was to evaluate the practical benefits of HLA and PTPN22 genetic testing for the assessment of disease recurrence risk in the Czech population. Methods: In 206 patients with GD, exon 2 in the HLA genes DRB1, DQA1, DQB1 and rs2476601 in the gene PTPN22 were sequenced. Results: The risk HLA haplotype DRB1*03-DQA1*05-DQB1*02 was more frequent in our GD patients than in the general European population. During long-term retrospective follow-up (many-year to lifelong perspective), 87 patients relapsed and 26 achieved remission lasting over 2 years indicating a 23% success rate for conservative treatment of the disease. In 93 people, the success of conservative treatment could not be evaluated (thyroidectomy immediately after the first attack or ongoing antithyroid therapy). Of the examined genes, the HLA-DQA1*05 variant reached statistical significance in terms of the ability to predict relapse (p=0.03). Combinations with either both other HLA risk genes forming the risk haplotype DRB1*03-DQA1*05-DQB1*02 or with the PTPN22 SNP did not improve the predictive value. Conclusion: the DQA1*05 variant may be a useful prognostic marker in patients with an unclear choice of treatment strategy.